Cross-linking of hyaluronic acid with 1, 2, 7, 8-diepoxyoctane. (November 2015) - Li, Z.; Ma, X.; Fan, D.; Zhu, C.; Zhao, L.; Liu, Y.; Chang, L.
Abstract : Hydrogels are usually achieved by cross-linking, which matters in tissue engineering. During the past decade, although various hydrogels have been synthesised using different cross-linking agents such as divinylsulphone and 1, 4-butanediol diglycidyl ether, some serious problems remain unresolved, especially excessive residuals. Here, we used 1, 2, 7, 8-diepoxyoctane as the cross-linker to prepare hyaluronic acid hydrogels and employed different biochemical methods to evaluate the performance of hyaluronic acid hydrogels. The results indicated that (1) hyaluronic acid hydrogels exhibited a proper swelling ratio suitable for filling a material; (2) The residual content of 1, 2, 7, 8-diepoxyoctane was ∼0.5–1.2 µg g −1, which was lower than industry standard; (3) The Cell Counting Kit-8 test revealed that hyaluronic acid hydrogels had no toxicity; (4) The vitro degradation test indicated that the residual weight of hyaluronic acid hydrogels was at least ∼46.9% after 4 weeks, which showed a potential to resist degradation. In conclusion, 1, 2, 7, 8-diepoxyoctane-cross-linked hyaluronic acid hydrogels could be used as a promising material in tissue engineering.